Detection and quantification of a release of carbon dioxide gas at the seafloor using pH eddy covariance and measurements of plume advection. (December 2021) - Koopmans, Dirk; Meyer, Volker; Schaap, Allison; Dewar, Marius; Färber, Paul; Long, Matthew; Gros, Jonas; Connelly, Douglas; Holtappels, Moritz
Highlights: ● We developed a pH eddy covariance system to detect a sub-seafloor CO2 release. ● It detected CO2 emission to the water column at injection rates of 5.7–143 kg d   −   1 . ● It was also sensitive enough to quantify benthic biological CO2 production. ● Close to bubble streams, the kinetics of aqueous CO2 equilibration are important. ● This system can be used to detect, attribute, and quantify seafloor sources of CO2 . Abstract: We detected a controlled release of CO2 (g) with pH eddy covariance. We quantified CO2 emission using measurements of water velocity and pH in the plume of aqueous CO2 generated by the bubble streams, and using model predictions of vertical CO2 dissolution and its dispersion downstream. CO2 (g) was injected 3 m below the floor of the North Sea at rates of 5.7–143 kg d   −   1 . Instruments were 2.6 m from the center of the bubble streams. In the absence of injected CO2, pH eddy covariance quantified the proton flux due to naturally-occurring benthic organic matter mineralization (equivalent to a dissolved inorganic carbon flux of 7.6 ± 3.3 mmol m   −   2 d   −   1, s.e., n  = 33). At the lowest injection rate, the proton flux due to CO2 dissolution was 20-fold greater than this. To accurately quantify emission, the kinetics of the carbonate system had to be accounted for. At the peak injection rate, 73 ± 13% (s.d.) of the injected CO2 was emitted, but when kinetics were neglected, the calculated CO2 emission was one-fifth of this. Our results demonstrate that geochemical techniques can detect and quantify very small seafloor sources of CO2 and attribute them to natural or abiotic origins.